The Effects of Early Girl-Child Marriage in Mutasa District- Manicaland Province: A Cases Of Samanga ‘A’Ward in Honde Valley - Kanjanda, Offard; Chiparange, Getrude Vongai (European Scientific Journal, ESJ, 2016)
Girl-child marriages in the developing countries of the world have caused a lot of suffering on the girl-children. According to Giddens (2009) issues of poverty, cultural practices, and political instability and gender inequalities have been noted as some of the major causes of girl-child marriages in developing countries. The situation has caused great concern to the communities of the global village because of the serious damages on the victims. Gage (2011) states that the status quo was exacerbated by the historical gender inequalities that continue to exist within families systems and place the girl-child an inferior citizen in her country. The girl-child remained vulnerable and segregated particularly, in educational advancement which is the key to self-empowerment, knowledge and skills development because of the high rate of girl-child marriage in the area. It appears there is little significant research on the matter in the developing countries. In order to establish some strategies to promote the girl-child’s life-skills a study was conducted in Samanga ‘A’ in Honde Valley in Manicaland Province- Zimbabwe. From a population of 1500 a sample size of 100 participants was selected using the cluster, systematic and purposive techniques because of their appropriateness to the two paradigms (Punch, 2009). Cluster technique was employed because the participants lived in different kraal-heads. The systematic technique was engaged because the participants were selected from every tenth household in each of the five kraal-heads. The purposive technique was used to select the influential participants such as local community leaders and the victims of early girl-child marriage. Marshall and Roseman (2006) support that purposive technique in qualitative study because the participants are powerful sources of information that is needed. Both qualitative and the quantitative paradigms were used in the study because some aspects of the study required simple response, while some of the questions demanded the participants’ in-depth knowledge on the problem (Newman, 2010). A case study methodology was adopted because of its ability to focus on a specific issue in a concerned area (Croll, 2010). Data were collected through the use of direct observation, questionnaire with both open and closed ended questions and interviews. The data were descriptively analysed. The research revealed that the prevalence of early girl-child marriage was perpetuated by the society’s cultural deprivation ideology which has since seen the girl-child discriminated in her efforts for self - empowerment through education. The study recommended that there is need for the government to enforce and implement gender-sensitive policies which aim at protecting the girl-child in-order to enhance economic, social, cultural and political transformation for sustainable development in the community.